The level [videorecording (DVD)] - Crome, Karla, 1989-; Haddock, Laura, 1985-; Clarke, Noel, 1975- (Acorn Media, 2017)
Detective Sergeant Nancy Devlin leads a double life. Her high-flying police career is at odds with an attachment to shady businessman and drug trafficker Frank Le Saux, who acts as a father figure to her. Having kept him off the police's radar for years, Nancy finds her secret at risk of exposure when Frank is murdered in Brighton and she's placed in the middle of the investigation, with a killer stalking her.